Effects of superelastic shape memory springs on the aeroelastic behavior of a typical airfoil section: passive vibration attenuation and energy harvesting applications - Sousa, Vagner Candido de (2016)
The modeling, analysis and experimental verification of a two-degree-of-freedom typical aeroelastic section with superelastic shape memory alloy springs are presented. The focus is to investigate the effects of the phase transformation of the shape memory alloy springs on the flutter and post-flutter behaviors of the typical section. The shape memory alloy phase transformation kinetics is described by a modified version of well-known phenomenological models. The shape memory alloy spring model is based on classical spring design (with the pure shear assumption) and modified to account for the nonlinear effects of phase transformation. The cross-section of the shape memory alloy wire is represented by a linear radial distribution of shear strain and nonlinear radial distributions of shear stress and martensitic fraction. The equations of motion of a linear typical section are modified to include the shape memory alloy springs. A linear unsteady aerodynamic model is employed to determine the aerodynamic loads. The proposed model is cast into state-space representation and solved with a Runge-Kutta method. It is numerically and experimentally shown that the phase transformation of shape memory alloy springs can be effectively exploited to enhance the aeroelastic behavior of a typical section by replacing unstable flutter oscillations by stable oscillations of acceptable amplitudes over a range of airflow speeds, providing a useful method of passive aeroelastic control. Since the modified aeroelastic behavior is attractive for wind energy harvesting purposes, electromechanical coupling is also modeled in the plunge degree-of-freedom along with a resistive load in the electrical domain for electrical power estimation. The exploitation of the shape memory alloy phase transformation is more attractive for airfoil-based wind energy harvesting performance than the use of typical concentrated nonlinearities (e.g., hardening steel) in terms of enhanced electrical power output.